PENERAPAN PASAL 5 AYAT (3) PERATURAN PEMERINTAH NOMOR 37 TAHUN 1998 TENTANG PERATURAN JABATAN PPAT, KEPALA DESA SEBAGAI PEJABAT PEMBUAT AKTA TANAH SEMENTARA (PPAT SEMENTARA) DI KABUPATEN BANYUASIN - Holilah holilah (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
Article 5 section 3 of Government regulation No 37/1998 about land certificate officer (PPAT) asserts that head of district has the authority to serve the society in establishing PPAT certificate in an area with less PPAT availability.Legal materials of this research will be taken from law regulation and research result which are interview and written data from participants. This research will use Statue Law Approach that examine the legal issues relate to Agrarian law No 5/1960, district law no 6/2014, government regulation no 37/1998 about PPAT position regulation, government regulation no 24/1997 about land registration, Ministry of Agrarian, Department of National Land Affairs no 1/1996 about PPAT formation, and Department of National Land Affairs regulation no 1/2006 about carrying out stipulation of the government regulation no 37/1998 about PPAT position regulation.  Case study approach is needed to answer the problem of head of village as temporary PPAT in relation to land right diversion in Banyuasin district